Studies on Salivary Fern Pattern during Estrous Cycle in Gir Cow and Jaffrabadi Buffalo - Padodara, Ramesh J; Vijyeta, Hardeepsinh P; Vasava, Amrita A.; Parikh, Suryakant S; Sharma, Arun K; Ramoliya, Urvashi B (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Bovine saliva changes its biochemical composition and biophysical properties due to the variations in sex steroid levels during the  estrous cycle. As a consequence of estrogen rise, saliva is produced in larger amounts at estrus - a stage also characterized by an  increase in mucus crystallization when observed under light microscopy. This study was aimed to provide information on the shape  and size of the crystallization of saliva and estrual mucus during entire estrous cycle in Gir cows and Jaffrabadi buffaloes (n=12 each)  and compare micrometry of their salivary crystallization patterns (SCP). The types of crystallization discriminated were: branch-like,  fern-like, fir-like, and a mixture of these. Branched patterns were observed more prominent in both saliva and mucus during the peak  estrus in both species. Score 3 of salivary and cervical mucus fern pattern was considered as the complete fern pattern at peak of the  estrus activity. Typical spur-like branching of SCP was the predominant in the cows, while in buffaloes the leaf shape of branching was  observed more. Based on SCP scale 1-3, the cows exhibited a longer estrus phase than buffaloes, also the pattern scale 2 and 3 were  significantly (p
Keywords: Crystallization; Fern pattern; Gir cow; Jaffrabadi buffalo; Saliva.